Genetic analysis of exon 3 of the leptin gene associated with reproductive traits in sheep (Ovis aries) based on GenBank DNA sequences - Hendro Sukoco; Agung Budiyanto; Aris Haryanto; Erif Maha Nugraha Setyawan; Suriansyah; Annisa Putri Cahyani; Salmin; Ferbian Milas Siswanto (Universitas Airlangga, 2026)
Polymorphisms in exon 3 of the leptin gene have been linked to reproductive and production traits in sheep. However, comprehensive in silico studies that combine comparative sequence analysis, phylogenetic relationships, gene expression profiling, and protein–protein interaction (PPI) networks across various sheep breeds remain limited. A total of 21 sheep leptin DNA sequences were extracted from NCBI GenBank. The leptin DNA sequences were aligned using BioEdit to identify single nucleotide polymorphisms (SNPs) and amino acid changes. Phylogenetic relationships among various sheep breeds were analyzed using Clustal Omega version 1.2.4. Leptin gene expression in sheep was analyzed using the Expression Atlas database, and leptin protein interactions with other proteins were evaluated using the STRING platform. The results showed that the leptin gene is highly expressed in the hypothalamus and moderately expressed in reproductive organs, highlighting its important role in regulating energy metabolism and reproductive function. Protein–protein interaction (PPI) analysis using STRING revealed a strong interaction between leptin and its receptor, which activates key signaling pathways, including the JAK2–STAT3, PI3K, and MAPK pathways. Genetic analysis revealed a predominance of missense mutations over silent mutations, with SNPs g.92G>A (Arginine→Glutamine) and g.208G>T (Valine→Leucine) appearing consistently across several breeds. Phylogenetic analysis also revealed substantial genetic diversity among sheep breeds, with clustering patterns reflecting distinct evolutionary origins. These findings demonstrate that integrating comparative genomics with functional bioinformatics analyses provides deeper insight into leptin exon 3 variation and serves as a comprehensive in silico framework for future functional validation and association studies in sheep.